PENGARUH KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP MOTIVASI KERJA KARYAWAN PADA PDAM PERUMDA TIRTA HIDAYAH KOTA BENGKULU - Anjel Dea Lola; Sri Ekowati (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine the effect of leadership and job satisfaction on employee work motivation at PDAM Perumda Tirta Hidayah, Bengkulu City. This study used a quantitative method with a sample of 130 respondents, using a total sampling technique. The data collection technique used a questionnaire. Data analysis techniques used multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing. The results show that leadership has a positive and significant effect on employee work motivation at PDAM Perumda Tirta Hidayah, Bengkulu City. This means that the higher the level of leadership, the more employee work motivation will increase. Job satisfaction has a positive and significant effect on employee work motivation at PDAM Perumda Tirta Hidayah, Bengkulu City. This means that the higher the level of employee job satisfaction, with things like salary, work relationships, opportunities for development, and recognition of work results, the higher the employee job satisfaction. And leadership and job satisfaction together have a positive and significant influence on employee work motivation at PDAM Perumda Tirta Hidayah, Bengkulu City. This means that with an effective leadership style and a high level of job satisfaction, work motivation will be more optimally increased. These two components work together and are very important to produce productive, loyal, and motivated employees. Keywords : Leadership, Job Satisfaction, Employee Work Motivation